2003
DOI: 10.1074/jbc.m211730200
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Expression of a Dominant Negative DNA Polymerase-γ Depletes Mitochondrial DNA and Produces a ρ0Phenotype

Abstract: We report the inducible, stable expression of a dominant negative form of mitochondria-specific DNA polymerase-␥ to eliminate mitochondrial DNA (mtDNA) from human cells in culture. HEK293 cells were transfected with a plasmid encoding inactive DNA polymerase-␥ harboring a D1135A substitution (POLGdn). The cells rapidly lost mtDNA (t1 ⁄2 ‫؍‬ 2-3 days) when expression of the transgene was induced. Concurrent reduction of mitochondrial encoded mRNA and protein, decreased cellular growth rate, and compromised resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 42 publications
4
57
0
Order By: Relevance
“…Additional data from the literature support this concept. Using an inducible dominant negative DNA polymerase ␥, Jazayeri et al (27) showed that decreasing mtDNA levels by 99% resulted in a reduction of the activity of the respiratory complexes to 18-30% of controls (27). In mice with a brain-specific Tfam knockout, which leads to lack of mtDNA replication, there was a 1-to 2-mo interval between severe mtDNA depletion and the detection of a biochemical defect (28).…”
Section: Discussionmentioning
confidence: 99%
“…Additional data from the literature support this concept. Using an inducible dominant negative DNA polymerase ␥, Jazayeri et al (27) showed that decreasing mtDNA levels by 99% resulted in a reduction of the activity of the respiratory complexes to 18-30% of controls (27). In mice with a brain-specific Tfam knockout, which leads to lack of mtDNA replication, there was a 1-to 2-mo interval between severe mtDNA depletion and the detection of a biochemical defect (28).…”
Section: Discussionmentioning
confidence: 99%
“…HeLa clones stably expressing shRNA targeting PNC1 exhibited a 40% and 60% reduction in protein did not show reduced proliferation (Figure 6b). Previous studies of mtDNA suppression after ethidium bromide treatment or suppression of critical components of the mtDNA maintenance machinery have shown impaired proliferation only when a critical level of mtDNA (less than 25% of initial content) is reached, which suggests that a minimal level of mtDNA is sufficient for cell proliferation (Jazayeri et al, 2003;Jeng et al, 2008). Interestingly, the effects of PNC1 on cell size and ROS production were not as tightly correlated with the degree of PNC1 suppression (Floyd et al, 2007 and this study).…”
Section: Pnc1 Regulates Mitochondrial Function and Emtmentioning
confidence: 98%
“…Alternative methods to deplete mtDNA and generate ρ 0 cells include mitochondrial targeting of the restriction endonuclease EcoRI 18 or expression of a dominant negative form of Polγ, a gene that codes for the catalytic subunit of the mitochondrial DNA polymerase 19 . However, these solutions do not circumvent a major drawback, which is that ρ 0 cells still contain functional mitochondria.…”
Section: Development Of An Assay That Allows the Generation Of Mitochmentioning
confidence: 99%